How do Real Exchange Rate Movements Affect the Economic Growth in Iran? - Zarei, Samira (International Journal of Contemporary Economics and Administrative Sciences, 2021)
This paper, through an asymmetric and non-linear framework, NARDL Model, investigates how real exchange rate movements affect the economic growth of Iran. In other words, whether the movements in the real exchange rate is an indicator of economic growth changes. Working on the monthly data of Gross Domestic Production (GDP) and Real Exchange Rate indexes from November 2009 to November 2019, this study shows asymmetric and negative relationships between exchange rate and economic growth both in the long run and short run. Although, in the long run, the magnitude of effects both positive and negative components of exchange rate on economic growth were significantly more than those of short run, the stability of the results have indicated that the roots of existing nonlinear and asymmetric relationships among these variables are so strong that change in time horizon, from the short run to long run, has also not been able to change them.